Study of the Titanium Dioxide Nanoparticles Used as UV absorber on Natural Herbal Extract Sunscreen Products - Wirunchit, Supamas; Sakulpeeb, Natchayaporn; Koetniyom, Wantana (My University, 2022)
This research focuses on the effects of UV absorber on natural herbal extracts including Wan Nga-chang (Ivory) and Wan Tan-diao containing Glycoside and Tannin with solvent prepared via the maceration method. The concentrations of UV absorber in this study, Titanium Dioxide (TiO2), were varied from 5, 10, 15 % by weight and compared to the unadded reference material. The characteristics and properties of sunscreen products were analyzed by UV-Vis spectroscopy, X-ray diffraction technique (XRD) and Fourier Transform-Infrared spectrometer (FT-IR). The results of the experiment showed that the optimal concentration of UV absorber is herbal cream and TiO2at concentrations of 10%wt. From XRD and FT-IR techniques confirmed the elements and functional group of herbal extract and TiO2, respectively.
Keywords: Natural Herbal Extract; Sunscreen Products; Titanium Dioxide Nanoparticles; UV-absorber